Rule-based Modelling and Tunable Resolution - Russ Harmer (Electronic Proceedings in Theoretical Computer Science, 2009)
We investigate the use of an extension of rule-based modelling for cellular signalling to create a structured space of model variants. This enables the incremental development of rule sets that start from simple mechanisms and which, by a gradual increase in agent and rule resolution, evolve into more detailed descriptions.